2016
DOI: 10.1016/j.nlm.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal–hippocampal pathways underlying inhibitory control over memory

Abstract: A key function of the prefrontal cortex is to support inhibitory control over behavior. It is widely believed that this function extends to stopping cognitive processes as well. Consistent with this, mounting evidence establishes the role of the right lateral prefrontal cortex in a clear case of cognitive control: retrieval suppression. Retrieval suppression refers to the ability to intentionally stop the retrieval process that arises when a reminder to a memory appears. Functional imaging data indicates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
166
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(194 citation statements)
references
References 173 publications
(243 reference statements)
14
166
0
Order By: Relevance
“…Cognitive alterations resulting from experimental manipulations of RE (i.e., lesions, reversible inactivation, optogenetic stimulation) support the idea that, instead of specifically affecting the functioning of either the mPFC or hippocampus, RE is mainly involved in orchestrating the flow of hippocampal-mPFC information, likely by modulating the coupling between both structures (Viana di Prisco and Vertes 2006;Saalmann 2014;Cassel and 4 Pereira Ito et al 2015;Pereira de Vasconcelos and Cassel 2015). The EC has also been shown to play a role in various cognitive tasks (e.g., Skelton and McNamara 1992;Sybirska et al 2000;Remondes and Schumann 2004;Brun et al 2008;Deshmuk and Knierum 2011;Suh et al 2011;Wilson et al 2013;Chao et al 2015;Anderson et al 2015), and both RE and EC appear to be involved in the consolidation of hippocampal-dependent memories (Remondes and Schumann 2004;Loureiro et al 2012). Moreover, Xu and Sűdhof (2013) have proposed that the cooperativity between RE-CA1 and EC-CA1 input may reduce the threshold for synaptic plasticity, and thus for the incorporation of entorhinal-transmitted neocortical information in hippocampal memory representation and subsequent long-term storage.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Cognitive alterations resulting from experimental manipulations of RE (i.e., lesions, reversible inactivation, optogenetic stimulation) support the idea that, instead of specifically affecting the functioning of either the mPFC or hippocampus, RE is mainly involved in orchestrating the flow of hippocampal-mPFC information, likely by modulating the coupling between both structures (Viana di Prisco and Vertes 2006;Saalmann 2014;Cassel and 4 Pereira Ito et al 2015;Pereira de Vasconcelos and Cassel 2015). The EC has also been shown to play a role in various cognitive tasks (e.g., Skelton and McNamara 1992;Sybirska et al 2000;Remondes and Schumann 2004;Brun et al 2008;Deshmuk and Knierum 2011;Suh et al 2011;Wilson et al 2013;Chao et al 2015;Anderson et al 2015), and both RE and EC appear to be involved in the consolidation of hippocampal-dependent memories (Remondes and Schumann 2004;Loureiro et al 2012). Moreover, Xu and Sűdhof (2013) have proposed that the cooperativity between RE-CA1 and EC-CA1 input may reduce the threshold for synaptic plasticity, and thus for the incorporation of entorhinal-transmitted neocortical information in hippocampal memory representation and subsequent long-term storage.…”
Section: Introductionmentioning
confidence: 84%
“…Recent studies have indicated the importance of RE for cognitive processes, such as behavioural flexibility, strategy shifting, inhibitory response control, associative learning, memory consolidation, working memory, fear memory, memory generalization, goal-directed navigation, and executive behaviours (Dollemanvan der Weel et al 2009;Davoodi et al 2011;Eleore et al 2011;Hembrook et al 2011;Kincheski et al 2012;Loureiro et al 2012;Cholvin et al 2013;Hallock et al 2013;Prasad et al 2013;Varela et al 2013;Wheeler et al 2013;Xu and Sűdhof 2013;Duan et al 2015;Griffin 2015;Ito et al 2015;Layfield et al 2015;Anderson et al 2015;Prasad et al 2016). This variety of memory-related behaviours has also been associated with the interplay between the medial prefrontal cortex (mPFC) and the hippocampus (Jin and Maren 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Given these observations, we suggest that the hippocampus contributes to selective inhibition of neocortical inhibitory engrams, providing a means to reactivate otherwise silent memories by selectively modulating EI balance in favor of excitation. On the other hand, the PFC is thought to be critical for directed forgetting (55) and may exert further top-down control over the hippocampus to prevent involuntary memory recall (53,56). Selective disinhibition, via the hippocampus or PFC, may be particularly critical when so-called "inhibitory control" is necessary to prevent recall following exposure to a cue that has the potential to trigger an unwanted memory (55).…”
Section: Inhibitory Engrams In Associative Memory Storage and Recallmentioning
confidence: 99%
“…On the other hand, the PFC is thought to be critical for directed forgetting (55) and may exert further top-down control over the hippocampus to prevent involuntary memory recall (53,56). Selective disinhibition, via the hippocampus or PFC, may be particularly critical when so-called "inhibitory control" is necessary to prevent recall following exposure to a cue that has the potential to trigger an unwanted memory (55). We further speculate that the precise contribution made by these two brain regions may depend on the age of a memory, with disinhibition for recent and remote memories showing greater dependence upon the hippocampus and PFC, respectively (57)(58)(59).…”
Section: Inhibitory Engrams In Associative Memory Storage and Recallmentioning
confidence: 99%
“…For example, reactivation within posterior parietal cortex (PPC) reflects detailed information about retrieved content (Kuhl and Chun, 2014;Lee et al, 2016). Reactivation within medial prefrontal cortex (mPFC) is thought to be of particular importance when past experience is compared with present experience (Kroes and Fernandez, 2012;Schlichting and Preston, 2015;Demblon et al, 2016;Richter et al, 2016) and connections between mPFC and hippocampus may provide the ideal scaffolding for a prediction generation and comparison system (Preston and Eichenbaum, 2013;Rajasethupathy et al, 2015;Anderson et al, 2016). Collectively, PPC and mPFC are part of the brain's so-called default mode network (DMN) and it has been argued that the DMN plays a central role in memory-based predictions (Bar, 2007(Bar, , 2009.…”
Section: Introductionmentioning
confidence: 99%